Comparative life cycle assessment (LCA) of bio-oil production from fast pyrolysis and hydrothermal liquefaction of oil palm empty fruit bunch (EFB) - Chan, Yi Herng (Animo Repository, 2016)
This paper presents a life cycle assessment of two alternative processes for the production of bio-oil from Malaysian oil palm empty fruit bunch (EFB), namely, fast pyrolysis and hydrothermal liquefaction, in which limited studies have been reported in the literature. In this study, both processes were evaluated and compared in terms of their impacts to the environment, specifically based on the selected impact categories: global warming potential (GWP), acidification, eutrophication, toxicity, and photochemical-oxidant formation. The results indicated that fast pyrolysis process of EFB caused more severe impact on the environment compared to hydrothermal liquefaction process. Fast pyrolysis process caused almost 50 % more GWP impact compared to hydrothermal liquefaction process, due to both high energy demand in the drying process and high-temperature operation of fast pyrolysis. Other than that, the assessment on other environmental impacts indicated that hydrothermal liquefaction operation is more environmentally benign compared to fast pyrolysis due to the reduced energy consumption. Lastly, sensitivity analysis involving three scenarios (change in bio-oil yield, thermal efficiency of boilers, and thermal efficiency of dryers), respectively, were constructed and presented. © 2016, Springer-Verlag Berlin Heidelberg.